Brand communication on Instagram during the COVID-19 pandemic: the Portuguese context - Andrade, José Gabriel (2022)
Social media, based on user-generated content, connectivity, and participation, have become a new environment for brands to capture attention and build lasting relationships with customers and fans. Participating in these platforms demanded a paradigmatic shift in branding and brand communication, which became more focused on listening to consumers and fans, interacting and collaborating with them, and nurturing mutually beneficial relationships. Digital influencers act as mediators between brands and their followers and play a pivotal role in social media marketing strategies. The COVID-19 pandemic, confinement periods imposed in many countries, and a reconfiguration of daily routines in post-confinement or deconfinement periods, had a profound impact on businesses, on consumption, and on branding. Many brands, unable to produce and market their products or offering their services for a considerable period, focused on their communication, on remaining relevant or becoming more relevant for their fans and customers. Brand communication on Instagram has changed during this short period, and our exploratory study sets out to map the main changes and to understand how brands, influencers and users perceive them, in the specific context of Portugal. This article presents results from an online survey to a purposive sample of 160 instagrammers, addressing their perceptions about the impact of these changes on their relationship with brands and influencers. We complement the perspective of users with interviews to 25 other relevant agents, namely Instagram influencers, marketing agencies and brands with relevant presence on Instagram.